Enhancing performance through music selection and thematic presentation in marching band competition: A case study in Pekan Olahraga Provinsi (PORPROV) XIV Jawa Barat - Noor Ayyuzia Khoirunnisa; Ganang Dwi Asmoro (Universitas Pendidikan Indonesia, 2023)
This study analyzes the performance of the West Bandung Regency contingent at the Pekan Olahraga Provinsi (PORPROV) XIV Jawa Barat. It specifically focuses on how the strategic integration of music selection and thematic presentation might improve the overall performance. The marching band sport involves teams competing in four competitions. The competitions include Lomba Baris Berbaris (LBB) Marching Competition, Lomba Unjuk Gelar (LUG), Lomba Berbaris Jarak Pendek / Short Distance Marching Competition (LBJP), and Lomba Ketahanan dan Ketepatan Berbaris (LKKB) / The Endurance and Accuracy Marching Competition. In order to effectively engage audiences and judges, bands must enhance and perfect their aesthetic and thematic techniques as the level of competition increases. The study utilized a qualitative research methodology, which involved active involvement and careful observation for analysis. We participated in marching band activities and closely observed practices and performances in order to acquire a thorough comprehension of the aesthetic and conceptual components. Data were gathered via observations, and discussions and examined using an analytical framework rooted in the literature on music aesthetics and performance art. This framework evaluated the elements of melody, harmony, rhythm, and visual depiction. The results emphasize the significance of carefully choosing music, maintaining theme consistency, and using visual components to provide a captivating performance. The topic chosen by the West Bandung contingent,